PERAN BURSA EFEK INDONESIA DALAM MEWUJUDKAN TRANSPARANSI PASAR MODAL - Pauzan; Nur Hidayat Fadhillah; Zulfikri Toguan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Indonesia Stock Exchange, as the institution responsible for securities trading, plays a central role in building a transparent, accountable, and trustworthy capital market ecosystem for all market participants. Transparency serves as the primary foundation that determines the quality of the capital market, as adequate information disclosure is an absolute prerequisite for investors to make rational investment decisions and avoid market manipulation. This study aims to analyze the role of the Indonesia Stock Exchange in achieving capital market transparency and to examine the legal protection mechanisms available to investors resulting from the success or failure of such transparency. The research method employed is a normative legal approach using legislative and conceptual frameworks. The results of the study indicate that the Indonesia Stock Exchange has established various transparency instruments; however, their implementation still faces serious challenges, particularly regarding the handling of suspensions, potential delistings, and the protection of minority shareholders. Strengthening regulations and institutional coordination are key to realizing a capital market that is truly transparent and equitable.